Original paperHelicobacter pylori IgG antibodies in association with secondary hyperparathyroidism in end-stage renal failure patients undergoing regular hemodialysis - Baradaran, Azar; Nasri, Hamid (Archives of Medical Science, 2005)
Helicobacter pylori (H. pylori) has been shown to play an important role in the development of gastritis and gastric ulcer. Excess parathyroid hormone (PTH) has long been considered detrimental to the health of patients with end-stage renal disease. PTH has been implicated as a multisystem uremic toxin, and hyperparathyroidism can be a debilitating complication in dialyzed patients. The aim of our study was the assessment of relationships between PTH abnormalities and concentration of IgG antibodies against H. pylori. The study included 44 (F=17, M=27) stable hemodialysis (HD) patients with upper gastrointestinal symptoms. Significant positive correlations between H. pylori IgG antibody titers with serum iPTH and phosphorus and significant inverse correlation of H. Pylori IgG antibody titers with serum alkalin phosphatase were found. Hyperparathyroidism is related with stimulation of gastrin synthesis as well with increased acidity of gastric juice. Hypergastrinaemia induced stimulation of gastrin synthesis and resultant increased acidity of gastric juice could intensify the H. pylori infection in HD patients. Further studies on the association of secondary hyperparathyroidism with helicobacter pylori infection are necessary, because both dyspeptic symptoms and secondary hyperparathyroidism are quite common in HD patients and in the meantime, more attention toward control of high levels of parathormone in HD patients is needed.